2004
DOI: 10.1055/s-2004-860866
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Weight Loss Surgeries on Liver Disease

Abstract: Obesity is the single most significant risk factor for the development of nonalcoholic fatty liver disease (NAFLD) in children and adults. NALFD is estimated to occur in 30 to 100% of obese adults, and in approximately 53% of obese children. The majority of obese patients have ultrasonographic evidence of fatty liver; 30% have histologically documented nonalcoholic steatohepatitis (NASH). Up to 25% of patients with NASH may progress to cirrhosis. In the United States, an estimated 65% of adults are overweight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 76 publications
2
19
0
1
Order By: Relevance
“…Other authors [46] have also described the high HL activity, although in postheparin plasma, this is a reflection of an altered lipoprotein profile in very obese women. In agreement with previous reports [47][48][49], we observed that following bariatric surgery, there was a drastic reduction in TAG levels in both the liver and plasma, as well as in levels of TC, although, here, this reduction was more marked than that found by other authors [50]. This reduction in the TAG content of hepatocytes is accompanied by a reduced amount of other lipids (TC, PL, etc.…”
Section: Discussionsupporting
confidence: 94%
“…Other authors [46] have also described the high HL activity, although in postheparin plasma, this is a reflection of an altered lipoprotein profile in very obese women. In agreement with previous reports [47][48][49], we observed that following bariatric surgery, there was a drastic reduction in TAG levels in both the liver and plasma, as well as in levels of TC, although, here, this reduction was more marked than that found by other authors [50]. This reduction in the TAG content of hepatocytes is accompanied by a reduced amount of other lipids (TC, PL, etc.…”
Section: Discussionsupporting
confidence: 94%
“…In agreement with previous reports [36][37][38], we observed that, following bariatric surgery, there was a drastic reduction in TAG levels in both liver and plasma, as well as in levels of TC, although in the present study, this reduction was more marked than that found by some authors [39]. This reduction in the TAG content in hepatocytes is accompanied by a reduced amount of other lipids (TC, PL, etc.…”
Section: Discussionsupporting
confidence: 93%
“…Many various conditions can be associated with NAFLD [2,3,5,13], and our case suggests that also VPA therapy may be considered. Our patient had no previous history of hepatic disease, and no other risk factors were present; therefore, it appears that the only factor for the development of NAFLD is VPA therapy.…”
Section: Discussionmentioning
confidence: 97%